Entanglement of Cape Fur Seals (Arctocephalus pusillus pusillus) in South Africa - Henry, Maguiña Ramilo (Department of Biological Sciences, 2023)
Global pollution is increasing, and marine mammals are commonly affected by the waste in the ocean. Endemic to the African continent, the pinniped species, Cape fur seal (Arctocephalus pusillus pusillus), are vulnerable to entanglement due to their curious nature and thick fur. Entanglement data were available from systematic photographic surveys of six colonies in South Africa (2019-2022) as well as opportunistic and citizen science records, photographs, aerial images and historical records from 1997 onwards. Overall, 314 cases of entangled seals were identified. As calculated from the systematic surveys, Baboon Point in Elands Bay (0.24% ± 0.78%, n = 7, with a 95% confidence interval) had the highest entanglement incidence. Seal Island in False Bay had the highest overall number of entanglements (50) and the highest mean number per survey (5.10 ± 0.46 number of entangled seals, n = 10), but this was also the largest colony assessed. Entanglement was observed the most in adults (61%, n = 189), with fishing materials being the primary cause of entanglements (40%, n = 59), specifically monofilament fishing lines (33%, n = 103). Although most entanglements were deemed ‘sight' (67%, n = 100), 28 cases (19%) were considered ‘severe,' likely impacting the health and welfare of affected individuals. Random Forest classification analysis identified the item of entangling material as an important predictor variable in terms of the severity level of the entanglement. The most common entangling material color was white (35%, n=82) followed by green (13%, n=30) and clear (7%, n=17) which may reflect the proportion of materials seals are exposed to, how they perceive them underwater, or their attraction to such colors. Aerial photographs showed higher efficiency in detecting entanglement cases than boat-based data where comparisons were possible. This is the first study to investigate entanglements of Cape fur seals in South Africa and highlights the need for correct disposal of waste, particularly that derived from the fishing industry, to mitigate its impacts on the welfare and conservation of marine fauna.